Unleashing Student Creativity: A Dynamic Look at Merdeka Belajar Curriculum's Impact - Wulandari, Yuli; S, Rustan; Ilham, Dodi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study explores the Implementation Analysis of the Merdeka Belajar Curriculum at SMKN 10 Luwu to foster creative and innovative students. The research delves into the curriculum implementation process, challenges faced, and outcomes through qualitative descriptive methods, including interviews and observations. Findings reveal successful implementation for the 2022/2023 academic year, showcasing teachers' proficiency in lesson planning and differentiated learning. Challenges include teachers' creative teaching methods, school environment considerations, and resource constraints. Addressing these requires training, community support, improved infrastructure, increased supervision, and collaboration. While the curriculum is effectively applied, refinement is ongoing, and some teachers encounter challenges in assessment timing. Despite this, teachers at SMKN 10 Luwu actively engage in the implementation process.